Usaha Pengembangan The Cut Room Barbershop Melalui Penilaian Konsumen - Rizky Herdianto; Lathifah Kurniawati (Parta: Jurnal Pengabdian Kepada Masyarakat, 2022)
Haircuts are certainly a necessity for every human being, especially men. Every year, of course, haircut styles always change in popularity, this is what causes barbershops to become fiercely competitive, especially barbershops. Barbershops are better known for having more up-to-date models and styles than barbershops in general. The more competition, the more problems arise, one of which is The Cut Room Barbershop which is rarely empty of visitors, but has difficulties in measuring the level of customer satisfaction and has problems in providing information to potential new customers. Through this activity, The Cut Room Barbershop can assess the level of customer satisfaction and can provide clear information for potential new customers. By providing media to accommodate consumer ratings and providing brief information on The Cut Room barbershop accounts, it is hoped that this can solve problems and expand the information network to get new customers.